ANALYSIS OF THE EFFECT OF MEDIA EXPOSURE, COMPANY SIZE, AND LEVERAGE ON CARBON EMISSION DISCLOSURE - Subadriyah, Subadriyah; Jannah, Miftakhul (Universitas PGRI Semarang, 2024)
This study aims to determine the influence of media exposure, company size and leverage on carbon emissions disclosure in manufacturing companies belonging to the listed industrial sub-sector. listed on the Indonesia Stock Exchange in the period 2019-2021. The research sample was 16 companies that met the criteria, in 3 years of observation there were 48 companies. Data collection was carried out using the documentary method. Collected research data were analyzed using descriptive analysis, classical hypothesis testing, multiple linear regression analysis and hypothesis testing. The results of this study show that media exposure and firm size have a positive effect on carbon emissions disclosure, while leverage has a negative effect on disclosure. carbon emissions.